UK government and politics for A-level - Lynch, Philip; Fairclough, Paul; Cooper, Toby (Hodder Education, 2022)
- Comprehensive coverage and analysis of relevant political developments helps develop students' knowledge and key skills -Up-to-date examples, case studies and debate feature will improve students' grasp of contemporary developments in UK politics -Includes more synoptic links to help students understand how different topics within the A-level link together -Includes quickfire knowledge-check questions and summaries of key content to help consolidate knowledge and understanding -Features exam-style questions throughout, helping students improve their analysis and evaluation skills -Provides answer guidance for exam-style questions online on the Hodder Education website.